Reporting Adverse Reactions of Skin Whitening Products in Wad- Medani Dermatology Hospital, Sudan - Mahgoub, Wegdan Yousif; Ibrahim, Abdelraheem Adam; Mahgoub, Jehan Yousif; Ahmed, Rana; M, Elmustafa (مجلة الجزيرة للعلوم الصحية; مجلد 16 عدد 1 (2020), 2020)
Background : There is growing concern about skin whitening both worldwide and in Sudan where there is no specific reporting system for the adverse reactions to whitening products. Objective: To identify adverse reactions associated with whitening products use through implementing an adverse reactions reporting system at the dermatology hospital in Wad -Medani, Sudan. Methods: A cross sectional study of patients presenting at the dermatology hospital in Wad-Medani, with adverse reactions (ARs) associated with the use of whitening products was done between October 2017 and September 2018.ARs reporting forms (containing socio-demographic characteristics, whitening products details and the detected ARs) were filled by the doctors attending both referral and out-patient clinics. Results: The study included 1000 patients aged 15- 48 years old, 98.5% of which were females. About 58% of patients had skin type VI, 32% skin type V and 10% skin type IV. More than 80% of the population used Hydroquinone and/or Clobetasol propionate or unlabeled mixtures of several whitening products bought from street vendors. Most patients (52%) used these products for more than 6 months. Acne, inflammation, ochronosis, hyperpigmentation, bacterial and fungal infections were the most reported ARs. The latter occurring in more than 42% of included patients. More than 68% of reported ARs were classified as severe by the treating doctors. Conclusion: S erious ARs of whitening products are prevalent and urgent measures are needed to address their irrational use. Vigilance ARs reporting systems are applicable and feasible which was evident since whitening products ARs reporting was continued even after the study was completed. The development and implementation of these systems should be adopted and encouraged by health authorities.